Complete genome sequence of Klebsiella oxytoca M1, isolated from Manripo area of South Korea - Shin, Sang Heum; Roh, Hanseong; Kim, Juhyeok; Cho, Sukhyeong; Um, Youngsoon; Lee, Jinwon; Ryu, Yeon-Woo; Chong, Hyonyong; Yang, Kap-Seok (Elsevier BV, 2015)
Here we report the full genome sequence of Klesiella oxytoca M1, isolated from Manripo area of South Korea. The strain K. oxytoca M1 is able to produce either 2,3-butanediol or acetoin selectively by controlling the pH and temperature. (C) 2015 Elsevier B.V. All rights reserved.